Analisis Perubahan Kebijakan Luar Negeri Cina Melalui Keikutsertaan Cina dalam Chiang Mai Initiative sebagai Respon Terhadap Dominasi Jepang di Asia Tenggara - Dharma Putri, Luh Paramitha; Sushanti, Sukma; Kumala Dewi, Putu Ratih (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2014), 2014)
ABSTRACT Asian financial crisis in 1997 marked as a momentum of new cooperation in East Asia especially on financial sector. Several arrangements were established during and after the crisis. In 2000, the ASEAN countries along with China, Japan, and South Korea launched Chiang Mai Initiative (CMI) as a financial assistance through bilateral swap agreements among members. This achievement shows the changing foreign policy of China since its rejection of Asian Monetary Fund (AMF) proposed by Japan during the crisis. This changing behavior of China is related to its relative position compared to Japan’s at that time. Due to that, Japan in this case remains as the key factor of China’s foreign policy decision making in East Asia. Using rational actor model and the concept of national interest, this research aims to analyze the changing foreign policy of China by joining CMI as its response to Japan. Keywords: China, Japan, Chiang Mai Initiative, Sino-Japanese Competition